1986
DOI: 10.2307/3899064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Progress through Hybridization of Induced and Natural Tetraploids in Crested Wheatgrass

Abstract: Because of restrictions imposed by crossing barriers, crested wheatgrass breeders have usually limited themselves to selection and hybridization within ploidy levels i.e., diploid (Zn=14), tetraploid (2n=28), or hexaploid (2n=42) populations. Several procedures have now been devised and evaluated to transfer genetic traits among ploidy levels, and interploidy breeding appears to be a feasible approach in the crested wheatgrass complex. Plant scientists with the USDA-ARS at Utah State University have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
(10 reference statements)
2
20
0
Order By: Relevance
“…Yield and IVDMD of Hycrest and 1-28 were greater than for the other entries tested. These yield responses were similar to those reported by Asay et al (1986) for several sites where yields of Hycrest were greater than Nordan and least for Fairway. Hycrest and 1-28 are similar in many respects, but differ from the 3 A. fragile selections as well as from Nordan and Fairway.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Yield and IVDMD of Hycrest and 1-28 were greater than for the other entries tested. These yield responses were similar to those reported by Asay et al (1986) for several sites where yields of Hycrest were greater than Nordan and least for Fairway. Hycrest and 1-28 are similar in many respects, but differ from the 3 A. fragile selections as well as from Nordan and Fairway.…”
Section: Discussionsupporting
confidence: 87%
“…Hycrest, Ephraim, 1-28, Ruff, and Syn-F have been developed since the 1970's (Asay et al 1986). Three of those grasses were included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cultivar was originally derived from a hybrid between an induced tetraploid form of A. cristatum and natural tetraploid A. desertorum (Asay et al 1986). The experiment was conducted at the Utah State University Evans Experimental Farm, 2 km south of Logan, Utah (41 45' N, III 48' W, at an altitude of 1,350 m above sea level).…”
Section: Methodsmentioning
confidence: 99%
“…Asay et al (1986) have demonstrated that hybridisation between ploidy levels may be an excellent way to develop improved germplasm of crested wheatgrass, utilising colchicine-induced tetraploids. Understanding the nature of polyploidy in this grass complex is important from taxonomic, phylogenetic and breeding standpoints.…”
Section: Introductionmentioning
confidence: 99%